Analisis Kebutuhan Data Alumni Berdasarkan Kriteria Sertifikasi AUN-QA - Gustina Bupatri; Mukhlidi Muskhir (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This research discusses the Study of Data Needs Analysis of PSPTEUNP Program Graduates in Accordance with AUN QA Criteria. This study aims to determine how the expected alumni data needs for PSPTE UNP graduates are in accordance with the AUN QA criteria. This research is a type of field research (field research) with a qualitative approach. Qualitative research is used to obtain deep data, data that contains meaning. Qualitative research is research that produces analytical procedures that do not use statistical analysis procedures or other quantification methods. Data collection techniques are observation, interviews, field observations, and documentation studies. The data analysis techniques used were data reduction, data presentation, conclusion, and verification. Based on the results of research on the need for data tracking of PSPTE graduates. From the results of the data obtained, graduates must have the latest innovations to open job opportunities for others related to their knowledge. The development of the latest industrial technology has also become a thought for graduates to be able to compete to become the needed experts. Based on the results of research data on data needs for graduates of the Electrical Engineering Education Study Program in accordance with the AUN-QA criteria. From several informants' opinions regarding the data needed by graduates, they do not meet the AUN-QA criteria.